Perceived performance of wood furniture small medium enterprises on innovative marketing strategies in Nigeria - Adamu, Umar Garba; Hussin, Siti Rahayu; Ismail, Noor Azlin (ARBN Asia, 2020)
Lack of innovative marketing strategy is one of the most common issues faced by small and medium-sized companies. Marketing strategy, tools, and tactics have been identified to be among the vulnerabilities of small and medium-sized businesses around the world. The study was conducted by introducing innovative marketing strategies to assess the perceived success of furniture owners as well as their adoption rate. In particular, the study examined the contribution of each elements, product, pricing promotion and distribution innovative strategies towards improving perceived output of furniture enterprises. 203 furniture makers were selected as a sample for the. 198 usable questionnaires were analysed. SPSS was employed as tools of analysis in determining the influence of each innovative marketing strategies and perceived performance. Outcomes indicate that furniture owners moderately adopted marketing innovation strategies and their performance is improving significantly. The paper concluded that since marketing innovation has been recognised as one of the basic ingredient of successful businesses, SMEs shuold aspire to incorporate this as part of their business lines. At the same time, further research will explore certain areas of innovative marketing to provide in-depth knowledge of new marketing strategies and tactics that could lead to better results for the small medium-sized company.